Key factors for Kazi Farms Kitchen to achieve leadership of the frozen (processed) food industry - Mohaimeen, Sadik (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.